THE PARADOX OF INDIVIDUALISM IN HIERARCHICAL ORGANISATIONS - Steeneveldt, Llewellyn Jude (My University, 2011)
Despite the rise of second wave organisational structures, organisational hierarchies have proven to be resilient and adaptive to change. Given this restrictive reality, grid-group cultural theory suggests that individualists will experience constraining social relations. The purpose of this study was to identify the factor conditions that result in the various coping strategies of individualists. A phenomenological strategy of inquiry was adopted, producing a description of the behavioural strategies of four individualists. Given sufficient factor conditions and an ability to cooperate with colleagues, the individualist was found to thrive. The corollary is that social relations were transformed such that the individualist chose to exit the organisation. Where exit was not viable, the individualist adopted a fatalistic bias, purging work life from the locus of actualisation. The study has validated grid-group cultural theory as an explanatory framework of behavioural strategies and has important implications for the management of organisational culture
MBA thesis - WBS
Keywords: Organisations, Hierarchical; Individualism